Expression and clinical relevance of paired box protein 7 and sex determining region Y-box 2 in canine corticotroph pituitary adenomas. Issue 3 (June 2015) - van Rijn, Sarah J.; Pouwer, Marianne G.; Tryfonidou, Marianna A.; Grinwis, Guy C.M.; van der Bend, Joanne E.E.; Beukers, Pauline E.P.F.; Vastenhout, Nadie; Drouin, Jacques; Penning, Louis C.; Meij, Björn P.
Highlights The expression of Pax7 and Sox2 was studied in canine pituitary adenomas. Pax7 expression was higher in enlarged pituitaries than in non-enlarged pituitaries. Downstream targets of Pax7 were significantly down regulated in adenoma samples. Pax7 and Sox2 are unsuitable as clinical prognosticators in canine Cushing's disease.